2022
DOI: 10.1111/desc.13256
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patterns of heterogeneity in executive functioning during adolescence: Evidence from population‐level data

Abstract: Executive functioning (EF) is fundamental to positive development. Yet, little is known about how to best characterize constellations of EF skills that may inform disparate associations between EF and behavior during adolescence. In the current study, cross‐validated latent profile analysis (LPA) was used to derive profiles of EF based on measures of inhibitory control, working memory, and cognitive flexibility using data from 11,672 youth (52.2% male, mean age = 9.91 years) in the Adolescent Brain and Cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 133 publications
2
8
0
Order By: Relevance
“…According to the unity/diversity framework, we assumed that moderate intercorrelations between the behavioral measures of (cool vs. hot) EF would remain evident within the unique latent profiles’ shapes. Due to past latent models and observations that cool EFs, particularly inhibition and working-memory updating, mature prior to hot EFs ( Lehto et al, 2003 ; Zelazo and Carlson, 2012 ; Karr et al, 2018 ; Wang et al, 2020 ; Chaku et al, 2022 ), the expected profiles included: (H1.1) an all-low EF profile and (H1.2) an all-high EF profile in which children consistently perform below or above the whole-sample average, respectively, across all five facets; (H1.3) a high-cool, low-hot EF profile in which children perform above-average on the three cool facets, but below-average on the two hot facets; and (H1.4) a high-inhibition or a high inhibition and updating profile in which children perform above-average on only these cool facets. These profiles would suggest different interrelations of individual developmental trajectories of cool and hot EF facets.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…According to the unity/diversity framework, we assumed that moderate intercorrelations between the behavioral measures of (cool vs. hot) EF would remain evident within the unique latent profiles’ shapes. Due to past latent models and observations that cool EFs, particularly inhibition and working-memory updating, mature prior to hot EFs ( Lehto et al, 2003 ; Zelazo and Carlson, 2012 ; Karr et al, 2018 ; Wang et al, 2020 ; Chaku et al, 2022 ), the expected profiles included: (H1.1) an all-low EF profile and (H1.2) an all-high EF profile in which children consistently perform below or above the whole-sample average, respectively, across all five facets; (H1.3) a high-cool, low-hot EF profile in which children perform above-average on the three cool facets, but below-average on the two hot facets; and (H1.4) a high-inhibition or a high inhibition and updating profile in which children perform above-average on only these cool facets. These profiles would suggest different interrelations of individual developmental trajectories of cool and hot EF facets.…”
Section: The Current Studymentioning
confidence: 99%
“…Latent person-oriented research is becoming more popular within developmental and cognitive psychology as it identifies meaningful subgroups within larger samples that deviate in their performance or characteristics from the sample’s mean and would otherwise be overlooked. Within a large cohort of children between 9 to 10 years, Chaku et al (2022) pinpointed four subgroups or latent profiles with different expressions of cool EF facets. Along with an average, a high, and a low EF profile, the authors identified a low inhibition profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaku et al. (2022) implemented a cross‐validated latent profile analysis and identified four different profiles of EF (i.e., average EF, high EF, low EF, and low inhibitory control). Boys, youth from low‐income households, and early developing youth were more likely to be characterized by a lower EF profile.…”
mentioning
confidence: 99%
“…These results indicate that distraction control is a highly dynamic process that qualitatively and quantitatively differs across age groups, highlighting the need for redefinitions of models of attention control to account for age-dependent rapid learning mechanisms. Chaku et al (2022) implemented a cross-validated latent profile analysis and identified four different profiles of EF (i.e., average EF, high EF, low EF, and low inhibitory control). Boys, youth from low-income households, and early developing youth were more likely to be characterized by a lower EF profile.…”
mentioning
confidence: 99%